Acute Ischemic Priapism: An AUA/SMSNA Guideline. Issue 5 (8th November 2021) - Bivalacqua, Trinity J.; Allen, Bryant K.; Brock, Gerald; Broderick, Gregory A.; Kohler, Tobias S.; Mulhall, John P.; Oristaglio, Jeff; Rahimi, Leila L.; Rogers, Zora R.; Terlecki, Ryan P.; Trost, Landon; Yafi, Faysal A.; et al.
Abstract : Purpose: Priapism is a persistent penile erection that continues hours beyond, or is unrelated to, sexual stimulation and results in a prolonged and uncontrolled erection. Given its time-dependent and progressive nature, priapism is a situation that both urologists and emergency medicine practitioners must be familiar with and comfortable managing. Acute ischemic priapism, characterized by little or no cavernous blood flow and abnormal cavernous blood gases (ie, hypoxic, hypercarbic, acidotic) represents a medical emergency and may lead to cavernosal fibrosis and subsequent erectile dysfunction. Materials and Methods: A comprehensive search of the literature was performed by Emergency Care Research Institute for articles published between January 1, 1960 and May 1, 2020. Searches identified 2948 potentially relevant articles, and 2516 of these were excluded at the title or abstract level for not meeting inclusion criteria for any key question. Full texts for the remaining 432 articles were reviewed, and ultimately 137 unique articles were included in the report. Results: This Guideline was developed to inform clinicians on the proper diagnosis and surgical and non-surgical treatment of patients with acute ischemic priapism. This Guideline addresses the role of imaging, adjunctive laboratory testing, early involvement of urologists when presenting to the emergency room, discussion of conservative therapies, enhanced data for patient counseling on risks of erectile dysfunction and surgical complications, specific recommendations on intracavernosal phenylephrine with or without irrigation, the inclusion of novel surgical techniques (eg, tunneling), and early penile prosthesis placement. Conclusions: All patients with priapism should be evaluated emergently to identify the sub-type of priapism (acute ischemic versus non-ischemic) and those with an acute ischemic event should be provided early intervention. Treatment of the acute ischemic patient must be based on patient objectives, available resources, and clinician experience. As such, a single pathway for managing the condition is oversimplified and no longer appropriate. Using a diversified approach, some men may be treated with intracavernosal injections of phenylephrine alone, others with aspiration/irrigation or distal shunting, and some may undergo non-emergent placement of a penile prosthesis.